1997
DOI: 10.1080/0013188970390204
|View full text |Cite
|
Sign up to set email alerts
|

The need for change in elementary school teacher training: the case of the energy concept as an example

Abstract: Do students in pre-service training programmes as elementary school teachers hold the correct scientific views, which will eventually allow them to plan and implement instructional strategies which, in turn, will lead their future pupils to achieve a scientific concept of energy? The results of a cross-college age study dealing with this issue is discussed in this paper. The energy conceptions of the students were analysed by means of a two-part written questionnaire, presented to them during the first week of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…As Trumper (1997) has found, many primary teachers' science knowledge base is deficient. Ginn and Waters (1995) argue that primary teachers should have a sound conceptual knowledge base in order to implement effective problem-solving strategies in the primary science classroom.…”
Section: Discussionmentioning
confidence: 98%
“…As Trumper (1997) has found, many primary teachers' science knowledge base is deficient. Ginn and Waters (1995) argue that primary teachers should have a sound conceptual knowledge base in order to implement effective problem-solving strategies in the primary science classroom.…”
Section: Discussionmentioning
confidence: 98%
“…In general, it has been found from these studies that environmental awareness among teachers is generally fair, although their reasoning of the underlying causes of environmental problems appears to be poor [26]. Regarding energy conceptions among teachers, Trumper [27] indicated that elementary school teachers in Israel had several misconceptions of energy and that their conceptual clarity of energy did not follow the scientifically accepted concepts. Diakidoy and Iordanou [23] also found that the knowledge of energy as a scientific concept among teachers and pre-service teachers in Cyprus was not very satisfactory and that the teachers had difficulties in distinguishing between concepts such as "energy" and "force".…”
Section: Literature Reviewmentioning
confidence: 98%
“…Numerous studies were conducted on this issue in order to reveal students' existing perceptions of energy concept (e.g. Watts, 1983;Duit, 1984;Driver & Warrington, 1985;Finegold & Trumper, 1989;Trumper, 1993Trumper, , 1996Trumper, , 1997aTrumper, , 1997bTrumper, , 1998Trumper & Gorsky, 1993;Goldring & Osborne, 1994;Odell, 1997;Konuk & Kılıç, 1999;Papadouris et al, 2004;Küçük et al, 2005;Köse et al, 2006;Ünal Çoban, et al, 2007;Hırça et al, 2008;Yuenyong et al, 2008;Boylan, 2008). As a result of these studies, different findings and results were obtained regarding the alternative conceptions of students.…”
Section: Introductionmentioning
confidence: 99%